Phase II Study of Sorafenib and Bortezomib for First-Line Treatment of Metastatic or Unresectable Renal Cell Carcinoma. (16th March 2015) - Rao, Arpit; Lauer, Richard
Abstract: Author Summary: Background: Sorafenib is an orally active multikinase inhibitor, and bortezomib is a proteasome inhibitor that affects multiple signaling pathways. Sorafenib has clinical activity in renal cell carcinoma (RCC), whereas bortezomib has demonstrated activity against RCC cell lines in vitro, with in vitro studies showing synergism between the two agents in the induction of apoptosis in neoplastic cell lines. In this phase II study, we explored the efficacy and toxicity of this regimen. Methods: Adult patients with cytologically confirmed clear cell RCC with no prior chemotherapy, Zubrod performance status of 0–1, serum creatinine <1.5 mg/dL, and normal liver function tests were treated with sorafenib 200 mg orally b.i.d. with bortezomib 1 mg/m 2 intravenously on days 1, 4, 8, and 11 every 21 days. Treatment was continued until disease progression or unacceptable toxicity. The primary objective was median progression-free survival (PFS) of at least 70 weeks. Results: Seventeen patients were enrolled between April 2011 and January 2013. Median age was 62 years (range: 44–75 years). Four of 17 patients had known brain metastasis on enrollment. Median number of cycles was 4 (range: 1 to ≥45). No patient had complete response, 1 had partial response, 12 had stable disease, and 4 had progressive disease (response rate of 6%; 95% confidence interval: 0%–29%) with treatment. Median PFS was 13.7 weeks, and median overall survival was 110 weeks. The study was halted for futility. Conclusion: The combination of sorafenib and bortezomib was well tolerated; however, response rate and PFS were comparable to sorafenib monotherapy. This regimen is not recommended for further development.